The LIM-domain-only protein LMO2 and its binding partner LDB1 are differentially required for class switch recombination - Beibei Yang; Yao Guo; Lilong Liu; Ting Huang; Bo Zhao; Wanyu Bai; Guigen Zhang; Chengming Zhu; Junchao Dong (Proceedings of the National Academy of Sciences, 2025)
The LIM-domain-only protein LMO2 interacts with LDB1 in context-dependent multiprotein complexes and plays key roles in erythropoiesis and T cell leukemogenesis, but whether they have any roles in B cells is unclear. Through a CRISPR/Cas9-based loss-of-function screening, we identified LMO2 and LDB1 as factors for class switch recombination (CSR) in murine B cells. LMO2 contributes to CSR at least in part by promoting end joining of DNA double-strand breaks (DSBs) and inhibiting end resection. Although LDB1 stabilizes LMO2 proteins, it is not required for end joining but functions as a positive regulator of AID transcription independent of LMO2, and this function of LDB1 requires its dimerization domain. Moreover, LDB1 directly binds to and promotes the looping of the AID promoter to upstream enhancers through dimerization. Our study revealed the mechanistically separated roles of LMO2 and LDB1 in different steps of CSR for antibody diversification.